2018
DOI: 10.1016/j.enggeo.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Geological discontinuity persistence: Implications and quantification

Abstract: Persistence of geological discontinuities is of great importance for many rock-related applications in earth sciences, both in terms of mechanical and hydraulic properties of individual discontinuities and fractured rock masses. Although the importance of persistence has been identified by academics and practitioners over the past decades, quantification of areal persistence remains extremely difficult; in practice, trace length from finite outcrop is still often used as an approximation for persistence. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(30 citation statements)
references
References 87 publications
(112 reference statements)
0
30
0
Order By: Relevance
“…Pre-existing discontinuities and their orientation, in relation with the orientation of excavation, determines the possible kinematic instability mode: some case studies regarding different kinds of quarry are reported in [38][39][40][41]. Stability conditions are further affected by discontinuity persistence in the form of rock bridges that can increase the available shear resistance [42][43][44]. Finally, the volume of detachable rock block is determined by spacing of rock joints.…”
Section: Failure Mode In Ornamental Stone Quarriesmentioning
confidence: 99%
“…Pre-existing discontinuities and their orientation, in relation with the orientation of excavation, determines the possible kinematic instability mode: some case studies regarding different kinds of quarry are reported in [38][39][40][41]. Stability conditions are further affected by discontinuity persistence in the form of rock bridges that can increase the available shear resistance [42][43][44]. Finally, the volume of detachable rock block is determined by spacing of rock joints.…”
Section: Failure Mode In Ornamental Stone Quarriesmentioning
confidence: 99%
“…In mining operations, the precise determinations of relevant fault geometries oriented to geotechnical design are a major concern for structural geologists and geotechnical engineers [1][2][3][4][5]. The principal uncertainties in structural and geomechanical models are mainly controlled by both limited data collection resolution [6] as well as the spatial distribution of data.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in practice, mining engineers must complete large interpretations during complex structural modeling by using software that can build multiple data-consistent solutions. This scenario has strong consequences in the mining value chain [5,7] affecting not only the geotechnical design, but also the hydrological management, blasting strategies, among others. Additionally, the transition in the mining operation from open-pit to the underground, i.e., OP to UG transition [8,9], triggers a requirement to improve the quality and precision of the structural and geomechanical models for an in-depth mining for hard rock masses (i.e., volcanic rocks) in which brittle slope failures are difficult to predict [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations